Early Sling Discontinuation Following Rotator Cuff Repair. Issue 3 (September 2018) - Kruse, Lisa M.; Falconer, Travis M.; Dimmick, Simon J.; Balestro, Jean C.; Cunningham, Greg; Cass, Ben; Young, Allan A.
Abstract : Following rotator cuff repair, patients typically are immobilized in a sling for 6 weeks with or without early motion. We hypothesize that early sling discontinuation at 2 weeks combined with rehabilitation protocol would not adversely affect clinical outcomes or tendon healing in small nonretracted rotator cuff tears following double-row repair. We prospectively evaluated 20 patients at 6 months postoperatively who underwent double-row rotator cuff repair for small nonretracted tears. Patients were immobilized in a sling for 2 weeks then allowed to remove the sling for daily activities below shoulder height. Formal rehabilitation started at 6 weeks. Patients were evaluated by physical examination, patient-rated outcomes (Constant-Morley Shoulder Scores, American Shoulder and Elbow Society score, Veterans Rand 36 General Health Survey), and magnetic resonance imaging. Average length of follow-up was 6 months. American Shoulder and Elbow Society scores increased an average of 32.2 points ( P <0.001), normalized Constant scores increased on average 31.5 points ( P <0.001), and Veterans Rand 36 General Health Survey physical scores improved on average 11.8 points ( P <0.001). Healing rate on magnetic resonance imaging was 95%. Early sling discontinuation following double-row rotator cuff repair did not result in adverse effects on the repaired rotator cuff tendons, and may be an acceptable option for small nonretracted rotator cuff tears in properly selected patients with a high likelihood of healing.